Family business succession planning: A case study of Malay legal firms in Malaysia - Abdul Aziz, Hassan (2014)
This dissertation represents an attempt to study how Malay entrepreneurs in Malaysia, in particular the family legal firms, plan the succession of the business to the next generation to ensure its future sustainability. The justification for researching the succession of legal firms was the continuity of legal firms was restricted by the ruling of the Legal Profession Act 1976, in that the owner of legal firm must always be a practicing lawyer. In addition, the succession of legal firms also becomes more difficult as they cannot be corporatized into private limited companies and must always be maintained as either a sole proprietorship or a partnership. A qualitative method approach was applied in this research methodology. Data was collected by way of interview from ten (10) case studies comprising founders of ten (10) Malay family legal firms who have been in active legal practice for more than 20 years and were expected to retire within five to ten years time. The significant finding of this study was that SMEs, like professional services-based firms, were not perceived as businesses and therefore could not be family businesses. Further, in such firms, there may be restrictions to succession as only “qualified persons”, relevant to the profession would be able to inherit the shares in the firm. Theoretically, this research contributes to academic knowledge by extending the definition of family business to include “a business which must be inheritable to family members in that it should be automatically transferable to family members without restriction, upon the demise of the founder or the incumbent owner”. Practically, the research could facilitate the Malay legal firms to plan succession leading to future business sustainability, by recommending that they build size, implement best management practices and finally transform themselves into multi-ethnic legal firms in Malaysia. In conclusion, the objective of successful succession is to have intergenerational business sustainability. As such, the research provides new insights and informs about the successful succession of Malay family legal firms, in particular, and Malay SMEs in Malaysia, in general, with the hope of achieving the Malay Corporate Equity Ownership target of 30 per cent of the total corporate equity ownership in Malaysia.